We know that

abc=-3
ab+bc+ac=-4
a+b+c=1

Find (a+b)(a+c)(b+c)

2 answers

(ab+bc+ac)(a+b+c) = a^2b + a^2c + ab^2 + ac^2 + b^2c + bc^2 + 3abc
(a+b)(a+c)(b+c) = a^2b + a^2c + ab^2 + ac^2 + b^2c + bc^2 + 2abc
subtract and you get
(ab+bc+ac)(a+b+c) - (a+b)(a+c)(b+c) = abc
I guess you can finish up now, eh?
Thank you sir
Similar Questions
  1. Given the function: f(x) = x^2 + 1 / x^2 - 9a)find y and x intercepts b) find the first derivative c) find any critical values
    1. answers icon 1 answer
  2. Given the function: f(x) = x^2 + 1 / x^2 - 9a)find y and x intercepts b) find the first derivative c) find any critical values
    1. answers icon 0 answers
  3. Let equation of an hyperbola be y^2-4x^2+4y+24x-41=0a. Find the standard form b. Find the center c. Find the vertices d. Find
    1. answers icon 0 answers
  4. For the following graph:a. Find the domain of f. b. Find the range of f. c. Find the x-intercepts. d. Find the y-intercept. e.
    1. answers icon 1 answer
more similar questions